Stomatal and non-stomatal limitations in savanna trees and C4 grasses grown at low, ambient and high atmospheric CO2. (September 2018) - Bellasio, Chandra; Quirk, Joe; Beerling, David J.
Highlights: Under a physiological watering–wetting cycle, C4 assimilation was limited by metabolic factors. These non-stomatal limitations were not alleviated by increasing growth [CO2]a . In C3 trees the assimilation was limited by stomatal factors. These stomatal limitations decreased substantially with increasing growth [CO2] a . Rising [CO2]a will reduce the competitiveness of C4 grasses to impinge on savanna vegetation. Abstract: By the end of the century, atmospheric CO2 concentration ([CO2 ]a ) could reach 800 ppm, having risen from ∼200 ppm ∼24 Myr ago. Carbon dioxide enters plant leaves through stomata that limit CO2 diffusion and assimilation, imposing stomatal limitation ( L S ). Other factors limiting assimilation are collectively called non-stomatal limitations ( L NS ). C4 photosynthesis concentrates CO2 around Rubisco, typically reducing L S . C4 -dominated savanna grasslands expanded under low [CO2 ]a and are metastable ecosystems where the response of trees and C4 grasses to rising [CO2 ]a will determine shifting vegetation patterns. How L S and L NS differ between savanna trees and C4 grasses under different [CO2 ]a will govern the responses of CO2 fixation and plant cover to [CO2 ]a – but quantitative comparisons are lacking. We measured assimilation, within soil wetting–drying cycles, of three C3 trees and three C4 grasses grown at 200, 400 or 800 ppm [CO2 ]a . Using assimilation–response curves, we resolved L S and L NS and show that rising [CO2 ]a alleviated L S, particularly for the C3 trees, but L NS was unaffected and remained substantially higher for the grasses across all [CO2 ]a treatments. Because L NS incurs higher metabolic costs and recovery compared with L S, our findings indicate that C4 grasses will be comparatively disadvantaged as [CO2 ]a rises.